The Guided Note-Taking Learning Model Effectively Improves Students' Mathematics Learning Creativity - Sardin, Sardin; Dewi, Santi Pranata; Saleh , Mohammed; Alrahhal, Maher (EDUPEDIA Publisher, 2023)
Student creativity in learning mathematics is one of the cognitive abilities that students need to master. The aim of this research is to determine and analyze students' mathematics learning creativity. This type of research is quasi-experimental. The population in this study were all class VII students at SMP Negeri 4 Baubau which consisted of 10 parallel classes with a total of 280 students. The sample in this research was taken using the Random Sampling technique. 28 students from class VII.10 were selected as the experimental class and 28 students from class VII.9 as the control class. The instruments used in this research were observation sheets and students' mathematics learning creativity tests. Data analysis uses descriptive analysis and inferential analysis. The hypothesis testing technique uses Independent Sample t-test analysis. The research results showed that the average pre-test for the experimental class was 43.57, while the post-test was 83.93. The control class pretest average was 46.61, while the post-test was 58.04. The results of the independent sample t-test were obtained t-count= 3,187 > t-table= 1.674 with a significance value of 0.045 < 0.05. It can be concluded that the GNT (Guided Note Taking) learning model is effective in increasing students' mathematics learning creativity. To increase students' creativity in mathematics learning, teachers should use learning media to build students' creativity concepts in visualizing the material being taught.